2018
DOI: 10.1007/s00221-018-5257-8
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements in interception with delayed visual feedback

Abstract: The increased reliance on electronic devices such as smartphones in our everyday life exposes us to various delays between our actions and their consequences. Whereas it is known that people can adapt to such delays, the mechanisms underlying such adaptation remain unclear. To better understand these mechanisms, the current study explored the role of eye movements in interception with delayed visual feedback. In two experiments, eye movements were recorded as participants tried to intercept a moving target wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…When participants could freely move their eyes, we observed that gaze was consistently oriented toward the target, not the cursor, as was observed previously when participants used a straightforward hand-cursor mapping (Danion and Flanagan 2018) or even a delayed hand-cursor mapping (Cámara et al 2018). This observation contrasts markedly with the changes in gaze behavior observed during the adaptation of hand reaching movements (Rentsch and Rand 2014).…”
Section: Free Gaze Behavior During Visuomotor Adaptationsupporting
confidence: 73%
“…When participants could freely move their eyes, we observed that gaze was consistently oriented toward the target, not the cursor, as was observed previously when participants used a straightforward hand-cursor mapping (Danion and Flanagan 2018) or even a delayed hand-cursor mapping (Cámara et al 2018). This observation contrasts markedly with the changes in gaze behavior observed during the adaptation of hand reaching movements (Rentsch and Rand 2014).…”
Section: Free Gaze Behavior During Visuomotor Adaptationsupporting
confidence: 73%
“…The second contrast compared NV vs NV2 also for the two electrodes, expecting no differences. Figure 1C and some previous studies [5,31] showed that participants' behaviour in the post-adaptation condition goes back to the same level observed in the pre-adaptation condition. As expected, the difference between NV and NV2 was not significant for both sites of coherence: (C3: diff=-0.008, t=-0.403, p=1.0; C4: diff=0.005, t=0.258, p=1.0).…”
Section: Figure 4 Neural Coherence For Both Groups Of Participants Dsupporting
confidence: 80%
“…In order to see whether participants relied on visual feedback of the cursor to try to intercept the target we looked at the temporal errors between the hand and the target at the moment the hand crossed the target's path [5,21,31]. The temporal error then is defined as the time difference between when the center of the target and when the hand cross the point at which the hand crosses the target's path ( Figure 1B).…”
Section: Experimental Design and Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations